Production, processing, and characterization of synthetic AAV gene therapy vectors - El Andari, Jihad; Grimm, Dirk (Biotechnology journal, 2021)
Over the last two decades, gene therapy vectors based on wild-type Adeno-associated viruses (AAV) are safe and efficacious in numerous clinical trials and are translated into three approved gene therapy products. Concomitantly, a large body of preclinical work has illustrated the power and potential of engineered synthetic AAV capsids that often excel in terms of an organ or cell specificity, the efficiency of in vitro or in vivo gene transfer, and/or reactivity with anti-AAV immune responses. In turn, this has created a demand for new, scalable, easy-to-implement, and plug-and-play platform processes that are compatible with the rapidly increasing range of AAV capsid variants. Here, the focus is on recent advances in methodologies for downstream processing and characterization of natural or synthetic AAV vectors, comprising different chromatography techniques and thermostability measurements. To illustrate the breadth of this portfolio, two chimeric capsids are used as representative examples that are derived through forward- or backwards-directed molecular evolution, namely, AAV-DJ and Anc80. Collectively, this ever-expanding arsenal of technologies promises to facilitate the development of the next AAV vector generation derived from synthetic capsids and to accelerate their manufacturing, and to thus boost the field of human gene therapy.
Published online: October 7, 2020
Gesehen am 19.10.2021